2014
DOI: 10.5812/ircmj.11698
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of QT Dispersion With Left Ventricular Mass Index in Early Diagnosis of Cardiac Dysfunction in Patients With β-Thalassemia Major

Abstract: Background:In electrocardiography (ECG), QT is the interval between the onset of Q wave to the end of the T wave. This interval may be a sign of changes in the ventricular structure in hematologic disorders such as thalassemia major.Objectives:The main goal of this study was to compare the diagnostic value of corrected QT dispersion (QTcd) and QT dispersion (QTd) with left ventricular mass (LVM) and left ventricular mass index (LVMI) as well as to determine their sensitivity and specificity in early detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“… 14 15 Left ventricular mass index (LVMI) as a left heart parameter had significant different values in case and control groups. 16 15 The results of the late studies were similar with the present study findings. Noori reported that echocardiographic parameters of left ventricle such as ICT, MPI, ET, PEP/ET, DT, AT, IRT, LVEDD, LVESD, and EF in patients and control groups were significantly different.…”
Section: Discussionsupporting
confidence: 90%
“… 14 15 Left ventricular mass index (LVMI) as a left heart parameter had significant different values in case and control groups. 16 15 The results of the late studies were similar with the present study findings. Noori reported that echocardiographic parameters of left ventricle such as ICT, MPI, ET, PEP/ET, DT, AT, IRT, LVEDD, LVESD, and EF in patients and control groups were significantly different.…”
Section: Discussionsupporting
confidence: 90%
“…Only case‐control studies, cross‐sectional studies and population‐based follow up studies with results on QT interval [mean (SD), measured by ECG] in cases (thalassaemia major patients) and controls (healthy individuals) were included. Eight studies fulfilled our criteria: Farahani et al (), Garadah et al (), Kayrak et al (), Magri et al (), Noori et al (), Oztarhan et al (), Russo et al () and Ulger et al (). The following data was extracted from each study: author, title, publication year, number of cases and controls, definition of cases, mean age of cases and controls, mean ferritin concentration of cases, mean QTc interval (SD) of cases and controls, and formula used for QT interval correction for heart rate.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular mortality is the leading cause of death in patients with secondary iron overload due to thalassaemia major and dependency of chronic blood transfusions (Borgna‐Pignatti et al , ). Studies have shown increased incidence of prolonged QT interval and sudden cardiac death among these patients(Yalcinkaya et al , ; Ulger et al , ; Detterich et al , ; Kayrak et al , ; Noori et al , ). As prolonged QT interval is a well‐known risk factor for development of ventricular tachycardia and sudden cardiac death, the association between increased iron stores and QT interval is worth further investigation.…”
mentioning
confidence: 99%
“…Mittal [20] also in agreement with Noori NM et al who showed that QTd was larger in case group than in control group. This study showed acceptable sensitivity and specificity of QTd in comparison to LVMI and suggests that standard ECG can be used for early diagnosis of cardiac involvement in asymptomatic patients with thalassemia major [21].…”
Section: Discussionmentioning
confidence: 70%